Advances in Cryogenic Engineering Materials
331 illus.
Keywords: The Third International Cryogenic Materials Conference (ICMC) was held in Madison, Wisconsin, in conjunction with the Cryogenic Engineering Conference (CEC) in August 1979. The University of Wisconsin hosted the two conferences in an excellent manner and deserves special recognition and praise. The synergism produced by conducting the two conferences simultaneously continues to be strong. Materials remain a demanding challenge and, in some cases, an obstacle to effective application of cryogenic technology. The association of materials specialists and cryogenic engineers every other year centers their attention on the most needed areas of research. The present ICMC Board met during the conference and elected two new members, E. W. Collings (U. S.) and D. Evans (England). The board voted to conduct two smaller, special-topic conferences in 1980. These are Filamentary A15 Superconductors, which was held at Brookhaven National Laboratories, Upton, New York in May 1980, and Fundamentals of Nonmetallics and Composites at Low Temperatures, held in Geneva, Switzerland in August 1980. The 1981 CEC/ICMC will be held August 10 through 14 in San Diego, California.